Vertical handoff decision algorithm for cooperation of multi-terminal based on fuzzy logic terminal - Gong-ye REN; Ji-hong ZHAO; Hua QU (Tongxin xuebao)
In order to solve the problem of vertical handoff decision for cooperation of multi-terminal,a fuzzy logic and AHP (analytic hierarchy process) based vertical handoff decision algorithm was proposed,which included the decision of the moment of triggering handoff and the construction of virtual terminal.Firstly,fuzzy logic was applied to decide the moment of triggering handoff.Secondly,a method combining AHP and SAW (simple additive weight) was used to choose the best composition manner of virtual terminal.Simulation results show that the proposed algorithm reduces the number of handoffs and the ratio of unnecessary handoffs.Additionally,it reflects application requirements and user preferences clearly.